Bequest Behavior and the Effect of Heirs' Earnings: Testing the Altruistic Model of Bequests - Wilhelm, Mark O. (American Economic Review, 1996)
That parents transfer resources to children because of altruistic concern is a reasonable a priori assumption. However, economic theories of altruistic transfers have produced many counterintuitive conclusions, and, consequently, much debate. When applied to bequests, these theories predict that inheritances will compensate for earnings differences between siblings as well as between parents and children. This paper tests these implications. Using a new data set centered on federal estate tax returns, little support can be found for an altruistic theory of bequests. This finding has implications for macroeconomic policy, government transfer programs, and inequality.